The Role of Social Capital in Socio-Economic Resistance of Tile Makers Families in Banjardowo - Nugraheni, Amalia Friska Dyah; Wijaya, Mahendra; Utami, Trisni (International Journal of Social Service and Research, 2023)
Professions in people's own lives are very diverse to achieve a better life, one of which is tile craftsmen. Nowadays there is a shift in the use of tiles, from what was originally traditional tiles to the main tiles in home making, the re-strengthening of social capital in building the economy of tile craftsmen through the sale of tiles is an important thing and needs to be considered. The objectives of this study are to analyze; (1) the role of social capital of tile craftsmen in tile production in Banjardowo, (2) the role of social capital of tile craftsmen in tile marketing in Banjardowo, (3) the driving and inhibiting factors of the role of tile craftsmen's social capital in the socioeconomic resilience of families, and (4) the role of social capital in the socioeconomic resilience of tile craftsmen's families in Banjardowo. This research uses qualitative research methods. The linking social capital that exists in tile craftsmen in the production process is that tile craftsmen in Dukuh Banjardowo have a direct relationship with other parties, namely the village, red soil suppliers, and capital providers (banks). Social capital linking is the cooperation of tile craftsmen with the village government and consumers. The driving factors in achieving the role of social capital are trust that is established between parties, trust in consumers and between parties, and there is support from the village government that is felt by tile craftsmen and the inhibiting factor is the transfer of land functions that provide shock to the production system.